Crabs in Bandealit Estuary Resort of Meru Betiri National Park - Galuh Paramita; Wachju Subchan; Vendi Eko Susilo (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2020)
Crabs are macrobenthos with characters that are attached to or resting on a base or live on basic sediments. The role of crabs in the ecosystem includes converting nutrients and enhancing mineralization, increasing the distribution of oxygen in the soil, helping carbon life cycles, and providing natural food for various types of aquatic biota. This research was conducted in the estuary area of ​​the Meru Betiri National Park (TNMB) Resort Bandealit. Identification results from 37 individual crabs at the Estuary Resort Bandealit Meru Betiri National Park (TNMB) obtained 5 species from 2 families (Portunidae and Sesarmidae). In the family Portunidae, there are 3 types, namely Scylla tranquebarica, Scylla paramamosain, and Scylla olivacea. Whereas in the family Sesarmidae found 2 types, namely Parasesarma pictum and Parasesarma cognatum. Keywords: Crab, Bandealit Resort, Identification